Development of titanium diaphragms for space propellant tank. Issue 1 (1st August 2022) - Zhang, Hai; Gu, Sendong; Zhang, Jianjun; Ouyang, Ruijie; Yu, Bin; Yang, Wenbo; Zhang, Xiao
Abstract: The fundamental structure of the space propellant tank is introduced. The design flow and the numerical simulation method of a typical metal diaphragm are proposed. Then, a range of 237mm diameter titanium diaphragms with different bottom fillet radiuses are designed. Based on the arc-length method, a series of finite element models of the reversal process of these titanium diaphragms are developed. With the aid of the models, this paper analyzes the effect of bottom fillet radius on pressures differential to roll the titanium diaphragms. The results show that the critical pressure increases with the decrease of the bottom fillet radius. A near linear increase is found, which indicated that the bottom fillet radius has a certain effect on the critical pressure. The maximum equivalent von mises stress increases with the decrease of the bottom fillet radius. The increase leads to the increase of the critical pressure. In addition, the deformation of the diaphragms becomes more and more instable with the decrease the bottom fillet radius.